2018
DOI: 10.1002/sim.7641
|View full text |Cite
|
Sign up to set email alerts
|

Design of cancer trials based on progression‐free survival with intermittent assessment

Abstract: Therapeutic advances in cancer mean that it is now impractical to performed phase III randomized trials evaluating experimental treatments on the basis of overall survival. As a result, the composite endpoint of progression-free survival has been routinely adopted in recent years as it is viewed as enabling a more timely and cost-effective approach to assessing the clinical benefit of novel interventions. This article considers design of cancer trials directed at the evaluation of treatment effects on progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…They found that accounting for interval censoring was not sufficient and recommend an illness-death model for interval-censored data which accounts for the possibility of developing recurrence between last visit and death Several solutions have been proposed in the literature for fitting regression models for component-wise censored composite endpoints. Zeng et al 15 focused on assessing the effect of a binary covariate on component-wise censored composite endpoint when both groups follow the same visit schedule. They showed that when you plan to analyze the data using the Cox model censored at last disease-free date, you need to inflate the sample size to maintain the power you would have had if progression time could be observed exactly, and they provide a sample size formula.…”
Section: Discussionmentioning
confidence: 99%
“…They found that accounting for interval censoring was not sufficient and recommend an illness-death model for interval-censored data which accounts for the possibility of developing recurrence between last visit and death Several solutions have been proposed in the literature for fitting regression models for component-wise censored composite endpoints. Zeng et al 15 focused on assessing the effect of a binary covariate on component-wise censored composite endpoint when both groups follow the same visit schedule. They showed that when you plan to analyze the data using the Cox model censored at last disease-free date, you need to inflate the sample size to maintain the power you would have had if progression time could be observed exactly, and they provide a sample size formula.…”
Section: Discussionmentioning
confidence: 99%
“…Often, in trials assessing PFS , assessments happen at regular intervals. How to account for that type of measurements in the likelihood is discussed by Zeng et al…”
Section: Statistical Inferencementioning
confidence: 99%
“…Panel data of this type, for which only snapshots of the underlying disease process are obtained, are interval censored, in that changes in health status can occur at some time point between assessments, and only part of the (latent) disease process is observed 12 . In cancer trials that use progression assessed via imaging or other tests, ignoring this interval censoring has been shown to result in sample size estimates that are up to 7.2% lower than required for the stated power 18 . Therefore, sample size estimation should consider interval censoring at the design stage, and MSM together with parametric transition models provide an appropriate method for accommodating it 10‐12 …”
Section: Introductionmentioning
confidence: 99%
“…Fifth, MSM can be used to assess the impact of frequency of assessments. A simulation study by Zeng et al explored efficiency gains due to increasing the frequency of patient assessments in an illness death model, concluding that, in their context, the gain in power was small in comparison to increasing the sample size 18 . Of note, their model constrained the well‐to‐disease progression and well‐to‐death transition intensities to be equal, with power estimates based on the effect of treatment on time to any transition out of the well state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation